A prospective natural history study of coronary atherosclerosis following liver transplantation. (March 2022) - Koshy, Anoop Ninan; Nerlekar, Nitesh; Gow, Paul John; Lim, Ruth; Smith, Gerard; Galea, Michael; Rodrigues, Thalys Sampaio; Lim, Han Sung; Teh, Andrew W.; Farouque, Omar
Abstract: Background & aims: Cardiovascular disease remains a leading cause of mortality following liver transplantation (LT). Whether it may be partially attributable to accelerated development of subclinical coronary artery disease is unclear. We sought to assess the longitudinal effect of LT on coronary plaque burden. Methods: A prospective observational study was conducted in 30 asymptomatic patients who underwent computed tomographic coronary angiography (CTCA) pre- and a median 4-years following LT. Serial changes were quantified using coronary artery calcium score (CACS) and semi-quantitative CTCA scores, in a blinded fashion. High-risk plaque (HRP) characteristics were also assessed. Plaque progression was defined using prognostically significant cut-offs. Results: In the study population (age 59.8 ± 8 years, 80% male), 93 of 459 coronary segments had plaque at baseline. On follow-up CTCA, 68 (+73.1%) new lesions appeared in segments without plaque initially. Nineteen (63.3%) patients demonstrated a clinically significant rise in plaque burden on CACS and semi-quantitative indices on CTCA (all p< 0.001). CAD-RADS score rose to ≥4 (≥70% stenosis) in 9 (30%) patients, necessitating ischemia-guided revascularization in 3 (10%) patients. While the absence of coronary calcification or plaque pre-LT was protective, presence of HRP and development of post-transplant metabolic syndrome were both strong independent predictors of atherosclerosis progression. Conclusions: Our findings suggest that LT is associated with early progression of coronary atherosclerosis. Accelerated progression was noted particularly in those with HRP and post-transplant metabolic syndrome. Understanding the mechanisms of this novel observation and the potential role of preventive cardiovascular therapies in this population merit further study. Graphical abstract: Figure illustrating rates of accelerated atherosclerosis following liver transplantation and the key clinical predictors. Image 1 Highlights: Liver transplantation is associated with development of adverse cardiometabolic sequelae. Despite this, the natural history of coronary atherosclerosis in liver transplant recipients has never been studied. A phenomenon of accelerated coronary atherosclerosis was noted in the majority of patients following liver transplantation. Understanding the mechanisms of this novel observation and the role of preventive therapies merits further investigation.